Propuesta de complementación de auditoria financiera como control interno en la empresa comercializadora de belleza Lili de la ciudad de Santa Marta, Colombia. - Miranda, Maria Jose; Pacheco, Paula Andrea (Universidad Antonio Nariño, 2022)
The present investigation is to design a Proposal for the Implementation of Financial Audit as Internal Control in the Lili Beauty Marketing Company of the City of Santa Marta, Colombia. This has as its main objective the financial audit as a control in the Lili Beauty Marketing company, which deals with the examination of the Financial Statements and is based on the regulations currently in force to deliver as a result an opinion or opinion on the data presented if they are justified and supported in a coherent, complete and concise manner. Because many companies in the commercial sector do not adequately carry out internal control. The present degree work is developed as follows: an analysis of similar investigations was carried out, they are previously done in order to determine some background. A theoretical framework has also been developed on which some concepts are fundamental. This project is carried out in several facets, the first is to find out why there is no control through audits, because the merchants are failing in that, after that analysis, the second is to find a way to implement these more often, since for a company works in an excellent way there must be constant verification, analysis and reliability of the financial statements, and thus avoid possible fraud or bankruptcy in the future.